Toll-like receptor 4 antagonist TAK-242 inhibits autoinflammatory symptoms in DITRA. (June 2017) - Shibata, Akitaka; Sugiura, Kazumitsu; Furuta, Yasuhide; Mukumoto, Yoshiko; Kaminuma, Osamu; Akiyama, Masashi
Abstract: Background: IL36RN encodes the IL-36 receptor antagonist (IL-36Ra), and loss-of-function mutations in IL36RN define a recessively inherited autoinflammatory disease named "deficiency of IL-36Ra" (DITRA). DITRA causes systemic autoinflammatory diseases, including generalized pustular psoriasis (GPP), an occasionally life-threatening disease that is characterized by widespread sterile pustules on the skin, fever and other systemic symptoms. GPP can present at any age, and provocative factors include various infections, medicines and pregnancy. Objective: We aimed to elucidate the role of toll-like receptor 4 (TLR4) signaling in DITRA and to innovate an efficient treatment for DITRA. Methods: We generated Il36rn −/− mice and treated them with TLR4 agonist to establish DITRA model mice. Furthermore, we administrated TLR4 antagonist TAK-242 to the model mice to inhibit the DITRA symptoms. Result: Il36rn − / − mice treated by TLR4 agonist showed autoinflammatory symptoms in skin, articulation and liver. Thus, we established model mice for DITRA or GPP that show cutaneous, articular, and hepatic autoinflammatory symptoms typical of DITRA or GPP: sterile pustules on the skin, liver abscesses and enthesitis of the hind paws. Additionally, these symptoms were canceled by TAK-242 administration. We demonstrated the inhibitory effects of the TLR4 antagonist TAK-242 on the autoinflammatory symptoms exhibited by the DITRA models. Conclusion: We suggested that blockage of TLR4 signaling is a promising treatment for DITRA and GPP. Highlights: Deficiency of IL-36 receptor antagonist (DITRA) model mice was established. The involvement of TLR4 signaling in the pathogenesis of DITRA was clearly demonstrated. Blockage of TLR4 signaling was shown as a promising treatment for DITRA.